Two Nucleolar Proteins, GDP1 and OLI2, Function As Ribosome Biogenesis Factors and Are Preferentially Involved in Promotion of Leaf Cell Proliferation without Strongly Affecting Leaf Adaxial–Abaxial Patterning in Arabidopsis thaliana - Kojima, Koji; Tamura, Junya; Chiba, Hiroto; Fukada, Kanae; Tsukaya, Hirokazu; Horiguchi, Gorou (Frontiers in Plant Science, 2018)
Leaf abaxial-adaxial patterning is dependent on the mutual repression of leaf polarity genes expressed either adaxially or abaxially. In Arabidopsis thaliana, this process is strongly affected by mutations in ribosomal protein genes and in ribosome biogenesis genes in a sensitized genetic background, such as asymmetric leaves2 (as2). Most ribosome-related mutants by themselves do not show leaf abaxialization, and one of their typical phenotypes is the formation of pointed rather than rounded leaves. In this study, we characterized two ribosome-related mutants to understand how ribosome biogenesis is linked to several aspects of leaf development. Previously, we isolated oligocellula2 (oli2) which exhibits the pointed-leaf phenotype and has a cell proliferation defect. OLI2 encodes a homolog of Nop2 in Saccharomyces cerevisiae, a ribosome biogenesis factor involved in pre-60S subunit maturation. In this study, we found another pointed-leaf mutant that carries a mutation in a gene encoding an uncharacterized protein with a G-patch domain. Similar to oli2, this mutant, named g-patch domain protein1 (gdp1), has a reduced number of leaf cells. In addition, gdp1 oli2 double mutants showed a strong genetic interaction such that they synergistically impaired cell proliferation in leaves and produced markedly larger cells. On the other hand, they showed additive phenotypes when combined with several known ribosomal protein mutants. Furthermore, these mutants have a defect in pre-rRNA processing. GDP1 and OLI2 are strongly expressed in tissues with high cell proliferation activity, and GDP1-GFP and GFP-OLI2 are localized in the nucleolus. These results suggest that OLI2 and GDP1 are involved in ribosome biogenesis. We then examined the effects of gdp1 and oli2 on adaxial-abaxial patterning by crossing them with as2. Interestingly, neither gdp1 nor oli2 strongly enhanced the leaf polarity defect of as2. Similar results were obtained with as2 gdp1 oli2 triple mutants although they showed severe growth defects. These results suggest that the leaf abaxialization phenotype induced by ribosome-related mutations is not merely the result of a general growth defect and that there may be a sensitive process in the ribosome biogenesis pathway that affects adaxial-abaxial patterning when compromised by a mutation.